SEBARAN SITUS PALEOLITIK DI TEPI ALIRAN SUNGAI WALENNAE, DI WILAYAH BONE BARAT, SULAWESI SELATAN - Budianto Hakim (WalennaE, 2018)
Almost all the palaeolithic sites in Cabbenge, Soppeng are on the banks of the Walennae River, both located on ancient river terraces as well as those that exist today. Considering the Walennae River is located in Bone District (Bontocani region), it is very possible in the Bone region connected to the Walennae River, there are palaeolithic sites that contemporary with the oldest occupancy in Soppeng District. This has been guided by the results of the thesis study of Archaeology Departement of Hasanuddin University students, in 1990 of Mallinrung area, Libureng, Bone, which reported the first time that lithic artefacts were found in the area, including those with the characteristics of palaeolithic technology. In the framework of expanding the potential area of palaeolithic archaeological remains on the banks of the Walennae River, this study focused on the Bone West region, including Bengo, Lamuru, Lappariaja, Kahu and Libureng Districts. Exploration surveys are intended to obtain information on the distribution of sites related to palaeolithic potential in the region. The results of the study showed the development of the technology of the palaeolithic stone tools, including flakes, hand-held axes, impact axes, and axe axes. Technological developments in stone tools and palaeolithic culture in the Bone West region, as well as showing palaeolithic cultural connectivity both in the Soppeng region and in the Old Walennae depressed regions, especially in the Bone West region. Hampir semua situs paleolitik di Cabbenge, Soppeng berada di tepi Sungai Walennae, baik yang terletak di teras sungai purba maupun yang ada sekarang ini. Mengingat Sungai Walennae berhulu di Kabupaten Bone (wilayah Bontocani), maka sangat memungkinkan  di wilayah Bone yang terkoneksi dengan Sungai Walennae, terdapat situs-situs paleolitik yang sejaman dengan masa hunian tertua di wialayah Kabupaten Soppeng. Hal ini telah dipandu oleh hasil penelitian skripsi mahasiswa arekeologi, Unhas tahun 1990 di wilayah Mallinrung, Libureng, Bone yang melaporkan pertama kali bahwa di daerah tersebut ditemukan artefak litik, termasuk yang memiliki ciri teknologi paleolitik. Dalam kerangka memperluas area potensi tinggalan arkeologi jaman paleolitik di tepi Sungai Walennae, penelitian ini  difokuskan pada wilayah Bone Barat, meliputi Kecamatan Bengo, Lamuru, Lappariaja, Kahu dan Libureng. Survei eksploratif dimaksudkan untuk memperoleh informasi sebaran situs terkait potensi paleolitik di wilayah tersebut. Hasil penelitian menunjukkan perkembangan teknologi alat batu paeolitik, diantaranya: alat serpih, kapak genggam, kapak perimbas, dan kapak penetak. Perkembangan teknologi alat batu dan budaya paleolitik di wilayah Bone Barat, sekaligus menunjukkan konektivitas budaya paleolitik baik di wilayah Soppeng maupun wilayah-wilayah depresi Walennae Purba khususnya di wilayah Bone Barat.